2020
DOI: 10.1088/2051-672x/ab82a3
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel method to characterize mean surface peak curvature as a signature of tribological performance of dental implant surfaces

Abstract: The integrity of dental implant surfaces might be compromised during surgical insertion. Wear and topographical modifications can occur during implant insertion, which can potentially have clinical implications. Accordingly, the analysis and prediction of the wear behaviour of dental implant surfaces is fundamental. Surface mean curvature is a key topographical parameter in contact mechanics, related to wear and plastic deformation; however, there is not a consensus on its characterization. In this paper, a cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Other applications are presented in reviews [200][201][202]. However, Zabala et al [203] found a limited ability of the Spc parameter to characterise dental implant surfaces.…”
Section: Feature Parametersmentioning
confidence: 99%
“…Other applications are presented in reviews [200][201][202]. However, Zabala et al [203] found a limited ability of the Spc parameter to characterise dental implant surfaces.…”
Section: Feature Parametersmentioning
confidence: 99%
“…It is common to find Ti ions at the level of peri-implant tissues, that are relatively higher in peri-implantitis sites compared to healthy implants. [ 21 22 ] Titanium dental implants are the most commonly used material in dentistry and is associated with antenna activity and the electromagnetic waves may produce harmful effects. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%